Pre-incisional epidural magnesium provides pre-emptive and postoperative analgesia in lower abdominal surgeries: a comparative study - Shrestha, Ninadini; Gurung, Renu; Marhatta, Moda Nath (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Magnesium sulphate has been used successfully as a non opioid analgesic adjuvant for postoperative pain management. This prospective controlled study was designed to evaluate the pre-emptive analgesic efficacy of adding magnesium to epidural analgesia in patients undergoing lower abdominal surgeries. Methodology: In a randomized, double- blind study sixty patients undergoing lower abdominal surgery under general anesthesia were assigned to three groups. Pre-magnesium (Group PI), post-magnesium (Group PO) and control (Group C) group. Anesthetic technique was standardized. Patients in pre-magnesium group received bolus of magnesium 50 mg via epidural before induction of anaesthesia followed by boluses of 10 mg h-1 until end of surgery. Post-magnesium group patients received epidural saline during the same time periods plus bolus epidural magnesium 50 mg at the end of surgery. Patients in control group received epidural saline during all three periods. Patients in the magnesium groups received bolus epidural analgesia with Fentanyl 8mcg, Bupivacaine 0.1%, and Magnesium 8mg in a volume of 8 ml after operation, when patient complained of pain and VAS score was more than 4. Patients in the control group received epidural analgesia with Fentanyl 8 mcg and Bupivacaine 0.1% in a volume of 8ml. Blood Pressure, pulse rate, respiratory rate, time to the first request for analgesic, visual analogue scale at rest, 24 hour, opioids consumption and side effect profiles were studied for 24 hours postoperatively. Results: The demographic parameters were comparable. Group PI had significantly lower VAS scores at all times 0,2,4,6,10,14,18 and 24 hours than those in the Group PO or Group C(P<0.05). The groups were similar with respect to haemodynamic, respiratory variables and side effects. Conclusion: Epidural Magnesium sulphate provided preemptive analgesia, and an a analgesic-sparing effect that improved postoperative analgesia without increasing the incidence of side-effects. Journal of Society of Anesthesiologists 2014 1(1): 22-28